Economic and Practical Aspects of the Use of Modern Management Methods in Hotels. A Case Study - Šebová, Ľubica; Chovanová, Klára; Marčeková, Radka; Švec, Adrián (Theoretical and Practical Research in Economic Fields, 2026)
Modern management methods have been extensively studied in the hospitality sector; however, empirical evidence from Central European post-transition economies remains limited. Recent studies from the region have examined general performance measurement practices or process management orientation, yet systematic data on the implementation of specific management tools in hotels have been largely absent. This study addresses this gap by investigating the adoption of five modern management methods - Benchmarking, Balanced Scorecard, Total Quality Management, Six Sigma, and Lean - in Slovak hotels. Based on a questionnaire survey of 56 hotels across different categories, ownership types, and sizes, the study employs non-parametric statistical methods (Kruskal-Wallis and Mann-Whitney tests) using SPSS software. The findings reveal that 38% of surveyed hotels actively use at least one modern management method, 41% plan to implement such methods, while 21% neither use nor plan to adopt them. Benchmarking emerges as the most widely adopted method (30%), followed by Balanced Scorecard (19%) and TQM (17%), whereas Six Sigma adoption remains marginal (9%). Statistical analysis found no significant differences in adoption rates across hotel categories, ownership types, or size classifications (p > 0.05). The study provides the first systematic empirical evidence on management method adoption in Slovak hotels and offers practical implications for hospitality managers and policymakers in the region.